2021
DOI: 10.1136/bmjopen-2020-041956
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare system maturity for integrated care: results of a Swiss nationwide survey using the SCIROCCO tool

Abstract: ObjectivesTo assess the maturity of the Swiss healthcare system for integrated care and to explore whether this maturity varied according to several variables.DesignA Swiss nationwide individual electronic survey in November 2019.Setting and populationStakeholders identified via lists of the Swiss Forum for Integrated Care and of the integrated care unit of the Swiss Federal Office of Public Health, and representatives of 26 cantonal public health departments, were invited to participate.Primary outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The open‐ended question was included in a cross‐sectional national survey conducted in Switzerland in the fall of 2019, with local healthcare stakeholders selected for their potential knowledge and experience of integrated care 10 . The survey was composed of three sections.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The open‐ended question was included in a cross‐sectional national survey conducted in Switzerland in the fall of 2019, with local healthcare stakeholders selected for their potential knowledge and experience of integrated care 10 . The survey was composed of three sections.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9] Considering that barriers to IC are context-specific and that the healthcare context has evolved a lot during the past decade, in terms of the burden of chronic diseases and the required shift in the chronic care paradigm, health policy targets and initiatives, an updated exploration of barriers to IC is appropriate to explore specificities in the swiss healthcare context. 10 The SCIROCCO tool, based on the B3-Maturity Model, 11 has been used to evaluate the maturity of health systems to deliver IC, by revealing their strengths, weaknesses and areas for improvement, through stakeholders' perspectives. 10,12,13 Recently, the SCIROCCO tool was included in a national survey to assess the "maturity" of the Swiss health system for IC.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent nationwide survey showed that the Swiss healthcare system's readiness for IC could be improved [43]. Indeed, seven of the SCIROCCO tool's [44] twelve items were rated as low (Readiness to Change, Structure and Governance, Standardisation and Simplification, Funding, Breadth of Ambition, Innovation Management and Capacity Building).…”
Section: Advances In Ic In Switzerlandmentioning
confidence: 99%